1952
DOI: 10.1139/v52-107
|View full text |Cite
|
Sign up to set email alerts
|

The Decomposition of Hypochlorous Acid

Abstract: The rate of decomposition of hypochloro~~s acid has been measured i n aqueous solution in the presence of much sodium hypochlorite. The rate is ilearly independent of the hypochlorite concentration, and proportional to the square of the hypochloro~~s acid concentration. Hence the mechanism proposed is 2HOC1+ HCI + HCIO? (both ionized), HOCl + C102-+ C1-+ HClOj (ionized).The first step is the slower. The reaction HOCl + CIO--+ C1-+ HClOn (ionized) also occurs, but is much slower. Oxygen is also evolved, by a hr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

1956
1956
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 1 publication
4
39
0
Order By: Relevance
“…The methods were the same as those outlined by the author in a previous paper (4 The general procedure in almost all runs was as follows. A quantity of the stock hypochlorite solution was poured into the reaction flask, the amount added being weighed to the nearest 0.1 gm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods were the same as those outlined by the author in a previous paper (4 The general procedure in almost all runs was as follows. A quantity of the stock hypochlorite solution was poured into the reaction flask, the amount added being weighed to the nearest 0.1 gm.…”
Section: Methodsmentioning
confidence: 99%
“…At very low sodium hydroxide concentrations hydrolysis t o hypochlorous acid and its decomposition become important; but the rate of this reaction has been measured (4), and it call be calculated that the sodium hydroxide would have to be close to 0.001 M before this reaction made much difference to the total rate. Can.…”
Section: 62mentioning
confidence: 99%
“…The apparatus was the same as described in the first paper on the uncatalyzed reaction (9). The analytical methods have been described in another previous paper (7).…”
Section: Experimen'i'al Methodsmentioning
confidence: 99%
“…Gray et al (1977) found an inverse dependence of Cu-catalyzed decomposition rates on [OH-] at very high Cuand OH-levels, i.e., 27 ppm and 1.3-7.0 M, respectively. All work reported herein was carried out at [OH-] = 0.03-0.05 M (typical of commercial hypochlorite solutions), which also avoided complications from the rapid decomposition of appreciable amounts of free HClO as would be found near neutrality (Lister, 1952;Adam et al, 1992).…”
Section: Introductionmentioning
confidence: 99%